FTKKP Champions Coastal Conservation, Empowering Ecosystems Through BASF Petronas Chemicals Mangrove Planting Project 2023 - Nur Aminatulmimi, Ismail; Azizul Helmi, Sofian (2023)
KUANTAN, 24 June 2023 - A remarkable collaboration took place as the passionate staff and enthusiastic students from the Faculty of Chemical and Process Engineering Technology (FTKKP) at Universiti Malaysia Pahang (UMP) united for an extraordinary cause.